Condition monitoring of underground cavern facilities - Lim, Andria Hwee Yi (2017)
The environment of power system operation differs between the underground facilities and the conventional aboveground. Unlike its aboveground counterpart, the underground power system faces relatively high humidity level, hot and saline environment, thus a conditional monitoring system as well as a reliability analysis of the underground power system is required. It is capable of analysing, monitoring, optimizing and predicting failures of power components such as transformers and cables.